Ethnoveterinary Survey Conducted in Baiku Yao Communities in Southwest China - Luo, Binsheng; Hu, Qimin; Lai, Kedao; Bhatt, Arvind; Hu, Renchuan (Frontiers in Veterinary Science, 2022)
Baiku Yao is a branch of the Yao ethnic group mainly living in Guangxi and Guizhou Province of China. They are recognized by UNESCO as one of the ethnic groups with intact ethnic culture. Baiku Yao holds rich ethnoveterinary knowledge, which they used to prevent and control various animal diseases. During the African swine fever outbreak, the livestock of the Baiku Yao community remains unaffected. We investigate the ethnoveterinary knowledge among the local Baiku Yao villagers. Total 39 ethnoveterinary plant species are reported to be utilized for treating various diseases. Five species namely Stephania kwangsiensis, Aristolochia kwangsiensis, Clerodendrum bungei, Paederia scandens and Tetradium ruticarpum have the highest relative frequency value. Strobilanthes cusia, Tetradium ruticarpum, and Stephania kwangsiensis are highly evaluated locally as anti-animal-plague medicine. The existing traditional ethnoveterinary knowledge needs to be conserved and validated scientifically.